POLITICAL OF THE ADMINISTRATION OF THE TIMURID EMPIRE DISTINCTIVE FEATURES (American Journal of Interdisciplinary Research and Development, 2022)
The fact that the Empire of Amir Timur was characterized by the fact that a complex, at the same time perfect system of government was formed in the interests of various strata. Amir Temur Empire, the fact that the centralized system of government is organized on the basis of political and legal teachings, which are omukhta with the values of Turkic peoples and Islamic traditions, the power of the Empire and its perfectly formed political-organizational management, military-legal system, socio-economic foundations embody the potential of the zabardast Turkic states is covered on the basis.